The Iconography of the Mythological Characters in the Divine Comedy Manuscripts of the 14th-15th Centuries: Functions and Iconographical Sources (Fenestella. Inside Medieval Art, 2024)
The history of illustration of Dante’s Divine Comedy in the 14th-15th centuries rarely attracts the attention of researchers. Nevertheless, a careful analysis of some manuscripts would clarify the genesis process of specific iconographic schemes within the framework of a very specific task: illustrating a text replete with figures of speech and references to ancient sources that were often unknown to the iconography designer. This contribute is devoted to the iconography of mythological characters found in Dante’s text and their visual sources based on a few manuscripts of the Divine Comedy dated from mid-14th and 15th centuries, six of which are fully illustrated.
Keywords: Divina Commedia; Dante Alighieri; Mythological characters; Medieval Iconography; Medieval manuscripts; Miniature painting; History of Medieval Art; Divine Commedy